Optimalisasi layanan berbasis teknologi informasi dalam rangka pencapaian pelayanan prima (excellent services) pada upt perpustakaan universitas negeri medan - Catur Dedek Khadijah (UIN Sumatera Utara, 2017)
This article discusses about Optimization of information technology-based services in order to achieve excellent service at library of medan state university. To be able to perform excellent service in the library, then the first step that must be done is to examine the client / learn the client to be more familiar with the client must be an important activity that can not be abandoned by the library. Through continuous and regularly revised client needs, a clearer picture of the client will be made, allowing librarians and libraries to prepare and provide library services tailored to the client's needs. This means that the library services offered can be utilized optimally by the client.Keywords: services, search, information Technology